Financial sector: Share of women in top decision-making bodies remains low - Elke Holst; Anja Kirsch (DIW Economic Bulletin, 2014)
At the end of 2014, women were no better represented on the top decision-making bodies of enterprises in the financial sector than the previous year. The share of women on the executive boards of the 100 largest banks and savings banks remained at an average of almost seven percent and on the executive boards of the 60 largest insurance companies at 8.5 percent. On supervisory boards, change was slow at best: Although the share of women in financial institutions was almost 18 percent and a good 17 percent among insurance companies, only decimal point increases could be observed. In public sector banks and savings banks, however, female representation on supervisory boards was greater than in the previous year: at almost 19 percent, the financial institutions in this sector are roughly on a par with private banks (a good 18 percent). Overall, the majority of women on supervisory boards are still employee representatives but shareholders have appointed considerably more women to supervisory boards in recent years. At European level, relatively few women were represented on the Council of the European Central Bank and on decision-making bodies of the national central banks, although there are significant differences across countries. Planned legislation on the equal participation of women and men in leadership positions in the private and public sectors aims to increase the proportion of women on supervisory boards of listed companies subject to codetermination regulations in Germany. The persistence of current structures could be greater in the financial sector than in the top 200 companies: Even though over half of financial sector employees are women, the share of women on the supervisory boards of financial institutions increased on average by less than 0.4 percentage points per year in the period 2006 to 2014, compared to 1.3 percentage points in the top 200 companies.
Keywords: G2; J16; J78; L32; M14; M51; 330; financial sector; board diversity; women CEOs; gender equality; gender quota; management; public and private banks; insurance companies; central banks